2007
DOI: 10.21608/jppp.2007.221189
|View full text |Cite
|
Sign up to set email alerts
|

WATER EXTRACTS OF SOME WILD PLANTS AS A MEAN OF NONE CHEMICAL CONTROL AGAINST THE TWO LAND SNAILS Monacha cartusiana (Müller) and Theba pisana (Müller) UNDER LABORATORY CONDITION.

Abstract: Water extracts from four wild plant species namely: Azadirachta indica, Neriu oleander, Calotropis procena, Urginea maritime (different parts: leaves, stems and flowers) were tested against two widely land snails species, i.e. Monacha cartusiana and Theba pisana under laboratory conditions. The concentrations used were crude extract 1:1 and the diluted 1:3 and 1:10. All the treatments were sprayed directly to the snails or sprayed to the lettuce leaves which used as poisonous food. Moreover, the grinded parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…In the present study, it is evident that the contact method is more effective than the dipping leaf method. This finding aligns with the observations of Abdel-Kader et al (2007), who investigated the efficacy of C. procera extract against two land snails, Monacha cartusiana and Theba pisana. The results indicated that the application of certain plant water extracts through spraying techniques was more efficient against land snails compared to incorporating the extracts into lettuce leaves as poisonous food or using the ground plant parts directly.…”
Section: Toxicological Influence Of Calotropis Procerasupporting
confidence: 91%
“…In the present study, it is evident that the contact method is more effective than the dipping leaf method. This finding aligns with the observations of Abdel-Kader et al (2007), who investigated the efficacy of C. procera extract against two land snails, Monacha cartusiana and Theba pisana. The results indicated that the application of certain plant water extracts through spraying techniques was more efficient against land snails compared to incorporating the extracts into lettuce leaves as poisonous food or using the ground plant parts directly.…”
Section: Toxicological Influence Of Calotropis Procerasupporting
confidence: 91%
“…In addition, using water extracts of Neem, Nerium, Apple of Sodom, and Red Squill as a spraying technique was more efficient against Carthusian and white garden snails than lettuce leaves as toxic meals or utilizing ground plant components directly (Abdel Kader et al, 2007). Our study indicated that aqueous extracts for Nerium (flowers and leaves) were enrolled with moderate percentage mortality which was (58.06 and 56.96%) respectively.…”
Section: Resultsmentioning
confidence: 67%
“…These differences in toxicity levels may have been due to various classes of compounds responsible for molluscicidal activities of plants. Abdel Kader et al (2007) found that using some plant water extracts with spraying was more efficient against land snails Monacha car tusiana (Müller) and Theba pisana (Müller) than using poisonous foods or grinding plant parts. Also, Ali et al (2013) studied the use of the aqueous extract of Sola num nigrum as a molluscicide to control the brown garden snail, Eobania vermiculata (Müller) under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%